2020
DOI: 10.1016/j.ctro.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

CONCORDE: A phase I platform study of novel agents in combination with conventional radiotherapy in non-small-cell lung cancer

Abstract: Lung cancer is the leading cause of cancer mortality worldwide and most patients are unsuitable for 'gold standard' treatment, which is concurrent chemoradiotherapy. CONCORDE is a platform study seeking to establish the toxicity profiles of multiple novel radiosensitisers targeting DNA repair proteins in patients treated with sequential chemoradiotherapy. Time-to-event continual reassessment will facilitate efficient dose-finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…For example, a study from the group at Queen’s University Belfast assessed the impact of AZD6738, an inhibitor of the ataxia telangiectasia related-3(ATRP) kinase in the DNA damage response, on tumor efficacy and late toxicity in the lung [30] . This study directly supported the translation of this approach to evaluate the safety of inhibitors of the DNA damage response in patients with non-small cell lung cancer through the CONDORDE trial (NCT04550104) [31] , [32] , [33] . Similarly, a study from Maastricht University demonstrated the efficacy of nintedanib in reducing radiation-induced lung fibrosis that subsequently led to multiple clinical trials (NCT02452463; NCT02496585) [34] , [35] .…”
Section: Discussionmentioning
confidence: 72%
“…For example, a study from the group at Queen’s University Belfast assessed the impact of AZD6738, an inhibitor of the ataxia telangiectasia related-3(ATRP) kinase in the DNA damage response, on tumor efficacy and late toxicity in the lung [30] . This study directly supported the translation of this approach to evaluate the safety of inhibitors of the DNA damage response in patients with non-small cell lung cancer through the CONDORDE trial (NCT04550104) [31] , [32] , [33] . Similarly, a study from Maastricht University demonstrated the efficacy of nintedanib in reducing radiation-induced lung fibrosis that subsequently led to multiple clinical trials (NCT02452463; NCT02496585) [34] , [35] .…”
Section: Discussionmentioning
confidence: 72%
“…However, platform or umbrella trials provide an opportunity to study multiple targeted therapies in the same disease area in a more efficient and scientifically rich manner [16] . A multi-arm phase IB platform study to determine the recommended phase II doses and safety profiles of up to five DNA damage response inhibitors given in combination with fixed dose curative-intent RT in patients with stage IIB/III NSCLC was recently funded by Cancer Research UK [35] . This platform will allow the study of multiple drugs in combination with RT in an efficient and scientifically rich manner with a planned associated translational research programme.…”
Section: Discussionmentioning
confidence: 99%
“…CONCORDE is designed using a Bayesian adaptive modelbased approach to dose escalation, with separate TiTE-CRM models for each experimental arm. 29 The primary objective is to determine the RP2D for each DDRi in combination with radical thoracic RT of 60 Gy in 30 fractions, on the basis of observed DLTs, defined in the Data Supplement. The DLT monitoring period is 13.5 months from the start of RT, divided into two periods: acute (up to 4.5 months post-RT start) and long (4.5 months to 13.5 months post-RT start).…”
Section: Design Summarymentioning
confidence: 99%
“…The protocol is described in elsewhere. 29 Here, we report in detail the statistical design and implementation of the TiTE-CRM (ISRCTN10142971).…”
Section: Introductionmentioning
confidence: 99%